Analysis of Factors Affecting the Interest in Investing in the Capital Market for Generation Z Students at Universitas Prima Indonesia - Calista Eugenia; Serlina; Louis Fernando; Agus Tina; Mahyudin (Journal Informatic, Education and Management (JIEM), 2025)
This study was motivated by the increasing access to and ease of financial technology, as well as the growing interest of the younger generation in investment instruments. The method used in this study was quantitative. Data were collected by distributing questionnaires to 100 students who met the purposive sampling criteria. The results of the partial regression test show that the four independent variables, namely technological progress, investment knowledge, investment returns, and risk tolerance, have a significant effect on investment interest. This is indicated by the significance value of each variable being less than 0.05. Simultaneously, the F test results show that the four variables together have a significant effect on investment interest with a calculated F value of 98.503 and a significance of 0.000. This study concludes that Gen Z students’ interest in investing in the capital market is significantly influenced by the factors of technology, knowledge, return, and risk.